2000
DOI: 10.1063/1.1288143
|View full text |Cite
|
Sign up to set email alerts
|

State-selected photodissociation dynamics of CS2+ in the C̃  2Σg+ state

Abstract: Articles you may be interested inDissociation of internal energy-selected methyl bromide ion revealed from threshold photoelectron-photoion coincidence velocity imaging J. Chem. Phys. 140, 044312 (2014); 10.1063/1.4862686Photodissociation mechanisms of the CO2 2+ dication studied using multi-state multiconfiguration second-order perturbation theory [1 + 1] photodissociation of CS 2 + ( X ̃ 2 Π g ) via the vibrationally mediated B ̃ 2 Σ u + state: Multichannels exhibiting and mode specific dynamics J. Chem. Phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Also listed in Table are the spectral data deduced from the emission spectrum 12 and the photoionization spectrum . Although the photoexcitation of the B̃ 2 Σ u + (000) ← X̃ 2 Π g,3/2 (000) transition was used in previous studies, the report about the photoexcitation spectrum of the B̃ 2 Σ u + (υ 1 υ 2 0) ← X̃ 2 Π g,3/2 (000) transition has gone largely unnoticed until now. Since the vibrational frequencies of CS 2 + have the approximation ν 1 ∼ 2ν 2 , Fermi resonance interaction is expected to occur between the (υ 1 ,υ 2 ,υ 3 ) and (υ 1 −1,υ 2 +2,υ 3 ) vibrational levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also listed in Table are the spectral data deduced from the emission spectrum 12 and the photoionization spectrum . Although the photoexcitation of the B̃ 2 Σ u + (000) ← X̃ 2 Π g,3/2 (000) transition was used in previous studies, the report about the photoexcitation spectrum of the B̃ 2 Σ u + (υ 1 υ 2 0) ← X̃ 2 Π g,3/2 (000) transition has gone largely unnoticed until now. Since the vibrational frequencies of CS 2 + have the approximation ν 1 ∼ 2ν 2 , Fermi resonance interaction is expected to occur between the (υ 1 ,υ 2 ,υ 3 ) and (υ 1 −1,υ 2 +2,υ 3 ) vibrational levels.…”
Section: Resultsmentioning
confidence: 99%
“…As an important species in astrophysics and atmospheric physics, the spectroscopy and dissociation dynamics of the linear CS 2 + ion have been studied by a variety of experimental techniques. Optical emission from the à and B̃ states of CS 2 + was observed, and the vibrational frequencies and rotational constants were precisely determined from the spectra. , The dissociation dynamics from the electronically excited states of CS 2 + were also studied by mass spectroscopy, electron impact technique, photoelectron photoion coincidence spectroscopy, and photofragment excitation spectroscopy. The C̃ state of CS 2 + was found to be totally predissociative and correlated to the CS + and S + fragment ions. Eland and co-workers 2 provide an interpretation for predissociation of the C̃ state, beginning with internal conversion to high vibrational levels of a lower state, perhaps the B̃ state (through odd ν 3 vibrational coupling), that is, the vibronic coupling between two electronic states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a one-photon 267-nm excitation process will not occur. According to the (2+1) REMPI experimental study by Morgan et al [15], [21].…”
Section: S T S T S T T T C T T Erf T T C T T Erf Tmentioning
confidence: 99%
“…Rydberg series were investigated in a wide range of excitation energies using the (2+1) and (3+1) REMPI methods [15]. In addition to the neutral CS 2 molecule, the structure and dynamics of the ground and excited ionic state, CS 2 + , have been investigated by several groups, using synchrotron-based pulse-field-ionization photoelectron spectroscopy [16], the photoelectron photoion coincidence technique [17], photofragment excitation spectroscopy [18][19][20], and the optical-optical double resonance technique [21]. These spectroscopic and dissociation studies demonstrated that CS 2 exhibits many typical physical processes within molecular system, such as spin-orbit coupling, Fermi resonance, intersystem crossing and internal conversion.…”
mentioning
confidence: 99%